The Anatomy of a University Physics Chapter: A TextualAnalysis of “Motion Along a Straight Line” and Its Implications for Science Reading - Soni Nurparijal; Arip Nurahman; Sufyan Aslam (English Education and Applied Linguistics Journal (EEAL Journal), 2026)
University introductory physics textbooks shape the content, vocabulary, and reasoning patterns students encounter, yet most textual analyses of text type, truth status, metalanguage, and scientific reasoning have examined junior high science textbooks, most notably Penney, Norris, Phillips, and Clark’s (2003) study. No study has directly applied Penney et al.’s four-part coding scheme to a university physics chapter, leaving open how such texts compare with the junior-high pattern. This study applied the Penney et al. (2003) framework to Chapter 2, “Motion Along a Straight Line,” from Young and Freedman’s University Physics (13th ed.). The chapter was coded sentence by sentence for text type, truth status, metalanguage, and scientific status/role in reasoning, with a second independent coding pass to check reliability. The chapter was overwhelmingly expository (approximately 79% of coded lines), but also contained a narrative component embodied in worked examples (approximately 15%) and a distinctive argumentative component in “Caution” boxes that refute misconceptions (approximately 6%); nearly all statements were true or explicitly flagged approximations, metalanguage was dense and mathematically inflected, and statements of fact or conclusion dominated the reasoning category, alongside explanation and supporting reasons concentrated in the Caution boxes. Textbook design at the introductory university level partially compensates for the near-total absence of argumentation reported for junior high textbooks, carrying implications for how future editions might more explicitly model scientific reasoning for students moving from narrative-rich to exposition-dominated science text.